2005
DOI: 10.1002/er.1052
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and economic analysis of heat storage application in co-generation systems

Abstract: SUMMARYThe possibility of improvement of the energy performance and economic feasibility of a CHP plant by the use of hot water storage tank is analysed in the paper. An energy balance of a system consisting of a CHP module, a peak boiler and a heat storage unit has been built and the storage efficiency has been defined. Heat transfer in storage tanks and its influence on the energy balance is discussed. A numerical model of heat transfer in the storage tank is presented. The thermodynamic and economic optimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
1
8
0
1
Order By: Relevance
“…It should be noted that 3 the tank will not be always full as in the case of the stratified tank, but it will be charged or discharged with water, changing 4 the volume of stored water continuously, according to the excess or shortage of heat demand. For the calculation of the 5 temperature evolution of the stored water the following energy conservation equation is applied [21]:…”
Section: Sizing Of the Installationmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that 3 the tank will not be always full as in the case of the stratified tank, but it will be charged or discharged with water, changing 4 the volume of stored water continuously, according to the excess or shortage of heat demand. For the calculation of the 5 temperature evolution of the stored water the following energy conservation equation is applied [21]:…”
Section: Sizing Of the Installationmentioning
confidence: 99%
“…This can also be 20 made clear in Figs. 7a, 7b, 8a and 8b where the cash flow charts of the middle and high sizing of the installation are shown 21 for the cases that the RHI is taken and is not taken into account, respectively. As can be seen in these graphs, the effect of the 22 these graphs in the 20 years of the investment is because the RHI is not provided after this period of time, so the income 1 consists only of the first two parts after the 20 th year of operation.…”
Section: Economic and Environmental Analysis 1mentioning
confidence: 99%
“…Based on system scenarios, the LOLE for both electric and total heat demands is given by (36) Moreover, the expected energy not supplied (EENS) is considered in this paper. This index represents the average energy not supplied when there is a loss of load.…”
Section: J Stochastic Reliability Indicesmentioning
confidence: 99%
“…The approximate investment costs of the boiler and heat-storage tank have been extracted from [35] and [36], respectively.…”
Section: Case Studymentioning
confidence: 99%
“…The study assumed 100% efficiency of hot water storage. Reviewed articles with similar aims included Baughman et al [6] and Kostowski and Skorek [7] who considered the thermodynamic, engineering and economic optimum capacity of TES for commercial applications. Baughman et al found that addition of a cold TES to an industrial plant had a substantial positive net present value (NPV), and the addition of absorption chillers and co-generation resulted in a significant additional improvement in NPV.…”
Section: Introductionmentioning
confidence: 99%